A randomized, open-label, Phase III study of obinutuzumab or rituximab plus CHOP in patients with previously untreated diffuse large B-Cell lymphoma: final analysis of GOYA - Sehn, Laurie H; Martelli, Maurizio; Trněný, Marek; Liu, Wenxin; Bolen, Christopher R; Knapp, Andrea; Sahin, Deniz; Sellam, Gila; Vitolo, Umberto (Journal of hematology & oncology, 2020)
BACKGROUND: Rituximab (R) plus cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) is the current standard therapy for diffuse large B cell lymphoma (DLBCL). Obinutuzumab (G), a glycoengineered, type II anti-CD20 monoclonal antibody, has shown activity and an acceptable safety profile when combined with CHOP (G-CHOP) in patients with advanced DLBCL. We present the final analysis results of the Phase III GOYA study (NCT01287741), which compared the efficacy and safety of G-CHOP versus R-CHOP in patients with previously untreated DLBCL. METHODS: Patients aged ≥ 18 years with previously untreated advanced DLBCL were randomly assigned to receive eight 21-day cycles of R or G, plus six or eight cycles of CHOP. The primary endpoint was investigator-assessed progression-free survival (PFS). Secondary endpoints included overall survival, other time-to-event endpoints, and safety; investigator-assessed PFS by cell of origin subgroup was an exploratory endpoint. RESULTS: A total of 1418 patients were randomized, with 1414 included in this final analysis (G-CHOP, N = 704; R-CHOP, N = 710). Five-year PFS rates were 63.8% and 62.6% for G-CHOP and R-CHOP, respectively (stratified hazard ratio 0.94, 95% CI 0.78-1.12; p = 0.48). The results of the secondary efficacy endpoints did not show a benefit of G-CHOP over R-CHOP. In the exploratory analysis, a trend towards benefit with G-CHOP over R-CHOP was apparent in the patients with germinal center B cell DLBCL. The safety profile of G-CHOP was as expected, and no new safety signals were observed. More grade 3-5 (75.1% vs 65.8%), serious (44.4% vs 38.4%), and fatal (6.1% vs 4.4%) adverse events (AEs) were observed in the G-CHOP arm compared with the R-CHOP arm, respectively, with the most common fatal AEs being infections. A higher incidence of late-onset neutropenia occurred in the G-CHOP arm (8.7%) versus the R-CHOP arm (4.9%). CONCLUSIONS: The final analysis, similar to the primary analysis, did not show a PFS benefit of G-CHOP over R-CHOP in previously untreated patients with DLBCL. The results of the secondary endpoints were consistent with the primary endpoint. Further exploratory analyses and investigation of biomarkers are ongoing.
Keywords: Diffuse large B cell lymphoma; Immunochemotherapy; Vincristine; Humans; lidé středního věku; Obinutuzumab; Outcomes; doxorubicin; Aged; mladý dospělý; dospělí; protokoly protinádorové kombinované chemoterapie; Female; Doxorubicin; Prednisone; senioři; lidé; humanizované monoklonální protilátky; doba přežití bez progrese choroby; Adult; prednison; Antibodies, Monoclonal, Humanized; ženské pohlaví; Kaplanův-Meierův odhad; Male; rituximab; difúzní velkobuněčný B-lymfom; vinkristin; Middle Aged; Adolescent; Antineoplastic Combined Chemotherapy Protocols; Aged, 80 and over; Cyclophosphamide; Lymphoma, Large B-Cell, Diffuse; Rituximab; Young Adult; senioři nad 80 let; Progression-Free Survival; Kaplan-Meier Estimate; mužské pohlaví; cyklofosfamid; mladiství